The Utilization of Diagnostic Musculoskeletal Ultrasound in the Evaluation of Gluteus Medius Tendon Pathology: A Perspective for Rehabilitation Providers - Robert C. Manske; Chris Wolfe; Phil Page; Michael L. Voight; Elizabeth Bardowski (North American Sports Medicine Institute, 2024)
Gluteus medius tendon pathology, encompassing tendinopathy and tears, is a significant source of lateral hip pain and functional impairment. Traditional diagnostic approaches have relied on clinical examination and magnetic resonance imaging (MRI). However, the advent of diagnostic musculoskeletal ultrasound (MSKUS) has transformed the evaluation process. Musculoskeletal ultrasound has emerged as a highly valuable diagnostic tool in the evaluation of gluteus medius tendon pathology, offering a non-invasive, cost-effective, and dynamic assessment method. This modality provides real-time visualization of soft tissue, enabling the detailed examination of tendon structure, vascularity, and associated musculature. For rehabilitation providers, understanding the application, strengths, and limitations of diagnostic MSKUS can enhance clinical decision-making, facilitate targeted therapeutic interventions, and potentially expedite the recovery process. This article reviews the application of MSKUS in diagnosing gluteus medius tendon pathology and its implications for rehabilitation practice. This should help to equip rehabilitation professionals with knowledge to better integrate this diagnostic tool into their clinical repertoire.